Self-awareness four years after severe traumatic brain injury: discordance between the patient's and relative's complaints. Results from the PariS-TBI study. (May 2018) - Chesnel, Camille; Jourdan, Claire; Bayen, Eleonore; Ghout, Idir; Darnoux, Emmanuelle; Azerad, Sylvie; Charanton, James; Aegerter, Philippe; Pradat-Diehl, Pascale; Ruet, Alexis; Azouvi, Philippe; Vallat-Azouvi, Claire
Objective: To evaluate the patient's awareness of his or her difficulties in the chronic phase of severe traumatic brain injury (TBI) and to determine the factors related to poor awareness. Design/Setting/Subjects: This study was part of a larger prospective inception cohort study of patients with severe TBI in the Parisian region (PariS-TBI study). Intervention/Main measures: Evaluation was carried out at four years and included the Brain Injury Complaint Questionnaire (BICoQ) completed by the patient and his or her relative as well as the evaluation of impairments, disability and quality of life. Results: A total of 90 patient-relative pairs were included. Lack of awareness was measured using the unawareness index that corresponded to the number of discordant results between the patient and relative in the direction of under evaluation of difficulties by the patient. The only significant relationship found with lack of awareness was the subjective burden perceived by the relative (Zarit Burden Inventory) ( r = 0.5; P < 0.00001). There was no significant relationship between lack of awareness and injury severity, pre-injury socio-demographic data, cognitive impairments, mood disorders, functional independence (Barthel index), global disability (Glasgow Outcome Scale), return to work at four years or quality of life (Quality Of Life after Brain Injury scale (QOLIBRI)). Conclusion: Lack of awareness four years post severe TBI was not related to the severity of the initial trauma, sociodemographic data, the severity of impairments, limitations of activity and participation, or the patient's quality of life. However, poor awareness did significantly influence the weight of the burden perceived by the relative.